The Effect of Covid-19 on Increasing E-Commerce Sales in Various Fields - Taufik Hidayat; Yasep Azzery (International Journal of Management Science and Application, 2022)
The Covid-19 pandemic forced the government to implement activity restriction obligations starting in March 2020. Even though Covid-19 paralysed physical activity, on the other hand, this has also made online sales increase sharply. According to the report "Big Data Review of the Impact of Covid-19 2020" compiled by the Central Statistics Agency (BPS), online sales during this pandemic actually jumped sharply when compared to sales in January 2020. In March 2020, online sales jumped 320 % of total online sales at the beginning of the year. The spikes are getting sharper, April 2020 online sales recorded an increase of 480% from January 2020.